Teaching Machines: The History of Personalized Learning, Audrey Watters (2021). Issue 1 (21st March 2023) - Clements, Joshua
Review of: Teaching Machines: The History of Personalized Learning, Audrey Watters (2021) Cambridge, MA: MIT Press, 316 pp., ISBN 978-0-26204-569-8, h/bk, 20.52 ISBN 978-0-26236-375-4, e-book, 21.99